The Comprehensive Model of Whistle-Blowing, Forensic Audit, Audit Investigation, and Fraud Detection - Atrisia Inayati Mamahit; Dekar Urumsah (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2018)
Fraud is a problem that has never been resolved from year to year. One type of fraud that often occurs in the government sector is corruption. Various attempts have been made by the government to detect fraud, but the efforts that have been made have not been effective in reducing fraud. This study aims to propose a conceptual model for detecting fraud by linking whistle-blowing, forensic audits, and investigation audits. The conceptual model of this research is expected to provide input to managers and decision makers regarding the factors that need to be considered in improving fraud detection so that in the future fraud prevention methods will be better and better.